2017
DOI: 10.1371/journal.pone.0184702
|View full text |Cite
|
Sign up to set email alerts
|

Multi-layered mutation in hedgehog-related genes in Gorlin syndrome may affect the phenotype

Abstract: Gorlin syndrome is a genetic disorder of autosomal dominant inheritance that predisposes the affected individual to a variety of disorders that are attributed largely to heterozygous germline patched1 (PTCH1) mutations. PTCH1 is a hedgehog (Hh) receptor as well as a repressor, mutation of which leads to constitutive activation of Hh pathway. Hh pathway encompasses a wide variety of cellular signaling cascades, which involve several molecules; however, no associated genotype-phenotype correlations have been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 46 publications
1
18
0
1
Order By: Relevance
“…Recently, it was shown that, in GS, causative gene mutations may exist in both PTCH1 and PTCH2 simultaneously. Onodera et al [ 34 ] detected mutations in PTCH2, BOC , and WNT9b genes along with PTCH1 by exome sequence analysis. These mutations are predicted to have a functional impact by programs called MutationTaster and Polyphen2 (Polymorphism Phenotyping v2), a web-based program to evaluate DNA sequence variants for their disease-causing potential.…”
Section: Genetic and Molecular Structural Aspects Of Gorlin Syndromentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that, in GS, causative gene mutations may exist in both PTCH1 and PTCH2 simultaneously. Onodera et al [ 34 ] detected mutations in PTCH2, BOC , and WNT9b genes along with PTCH1 by exome sequence analysis. These mutations are predicted to have a functional impact by programs called MutationTaster and Polyphen2 (Polymorphism Phenotyping v2), a web-based program to evaluate DNA sequence variants for their disease-causing potential.…”
Section: Genetic and Molecular Structural Aspects Of Gorlin Syndromentioning
confidence: 99%
“…These mutations are predicted to have a functional impact by programs called MutationTaster and Polyphen2 (Polymorphism Phenotyping v2), a web-based program to evaluate DNA sequence variants for their disease-causing potential. These results indicate that some patients with GS might have mutilayered mutations in the Hh signaling pathway [ 34 ].…”
Section: Genetic and Molecular Structural Aspects Of Gorlin Syndromentioning
confidence: 99%
“…However, another possibility is that the difference in phenotype between these case series was due to multilayered variants in genes related to the hedgehog pathway as hypothesized by Onodera et al . [10], radiation exposure, and possibly pigmentation genes. In Onodera et al's study of four patients with GS and PTCH1 variants they found that all patients had additional variants in genes related to the hedgehog pathway [10].…”
Section: Discussionmentioning
confidence: 99%
“…SUFU pathogenic variants are associated with a higher rate of meningiomas and medulloblastomas compared to PTCH1 [4, 9]. Studies have also shown that some of the variability seen in GS might be due to multilayered genetic variants in the hedgehog pathway related genes [10].…”
Section: Introductionmentioning
confidence: 99%
“…The missing relationship between the genotype and the phenotype suggests the existence of a very complex variability of this syndrome, possibly originated by the interaction of genetic background and environmental factors [2,44,45]. However, it has been proposed that additional simultaneous mutation may contribute to phenotype variation [46].…”
Section: Genetic Aspectsmentioning
confidence: 99%